2019
DOI: 10.1111/mve.12385
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometric analysis of the effect of temperature on wing size and shape in Aedes albopictus

Abstract: Wing geometry helps to identify mosquito species, even cryptic ones. On the other hand, temperature has a well‐known effect on insect metric properties. Can such effects blur the taxonomic signal embedded in the wing? Two strains of Aedes albopictus (laboratory and field strain) were examined under three different rearing temperatures (26, 30 and 33 °C) using landmark‐ and outline‐based morphometric approaches. The wings of each experimental line were compared with Aedes aegypti. Both approaches indicated simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 39 publications
0
20
1
1
Order By: Relevance
“…Mosquito size can be directly influenced by environmental conditions undergone during larval development [3]. Individuals reared at higher temperatures are expected to have smaller wings [28, 30]. A previous study carried out in the same area already showed that altitude can be a proxy for temperature, which may impact the oviposition activity of Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquito size can be directly influenced by environmental conditions undergone during larval development [3]. Individuals reared at higher temperatures are expected to have smaller wings [28, 30]. A previous study carried out in the same area already showed that altitude can be a proxy for temperature, which may impact the oviposition activity of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…For males and females, the size and shape analysis indicated significant differences among altitudinal populations. This result is most probably associated with biological [18] and/or environmental factors such as different blood sources (different host populations available between stations), ecological factors like different microhabitats [27], ecosystem vegetation [13], and/or climatic effects such as temperature differences between altitudes groups [11,26,28].…”
Section: Discussionmentioning
confidence: 99%
“…In recent publications referring to biological databases, Dujardin et al (2010); Garros and Dujardin (2013) report on the importance of creating DBs related to the use of the mosquito wing geometric morphometry (WGM) technique. In addition, Lorenz et al (2017); Jaramillo Wilke et al (2016), among other several authors (Calle et al, 2002;Jirakanjanakit and Dujardin, 2005;Dujardin, 2008;Jirakanjanakit et al, 2008;Henry et al, 2010;Vidal et al, 2011;Motoki et al, 2012;Vidal and Suesdek, 2012;Yeap et al, 2013;Börstler et al, 2014;Laurito et al, 2015;Phanitchat et al, 2019;Chaiphongpachara and Laojun, 2020;Sauer et al, 2020;Carvajal et al, 2021) who have already used to solve biological problems in Culicidae, directly and indirectly, reinforce the importance of gathering morphological, ecological and space-time data related to mosquitoes in a DB. The WingBank can enable studies of reanalysis and meta-analysis, micro and macroevolutionary and that can also contribute to integrative taxonomy, a multidisciplinary approach defended by several authors as the best approach for the diagnosis of species (Schlick-Steiner et al, 2010;Garros and Dujardin, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…Geographically separated populations of the same species can have significant intraspecific variation in their wing morphology 22 , 56 , 57 . Furthermore, abiotic and biotic conditions of breeding habitats can influence the wing geometry through carry-over effects from the immature to the adult stage 58 61 . Those factors have to be kept in mind when choosing mosquito specimens for the analyses of species-specific wing patterns.…”
Section: Discussionmentioning
confidence: 99%